Cell Size-Dependent Effects of Solar UV Radiation on Primary Production in Coastal Waters of the South China Sea - Li, Gang; Gao, Kunshan; 高坤山 (SPRINGER, 2013)
National Natural Science Foundation [40930846, 41120164007, 41206132]; National Basic Research Program of China [2009CB421207]; Program for Changjiang Scholars and Innovative Research Team [IRT0941]; MOST [S2012GR0290]; Special Research Fund for the National Non-profit Institutes [2008M15]; CAS [SQ201115] In order to examine the effects of solar ultraviolet radiation (UVR, 280-400 nm) on photosynthesis of differently cell-sized phytoplankton, natural phytoplankton assemblages from the coastal waters of the South China Sea were separated into three groups (> 20, 5-20, and < 5 mu m) and exposed to four different solar UV spectral regimes, i.e., 280-700 nm (PAR + UVR), 400-700 nm (PAR), 280-400 nm (UV-A + B), and 315-400 nm (UV-A). In situ carbon fixation measurements revealed that microplankton (> 20 mu m) efficiently utilized UV-A for photosynthetic carbon fixation, with assimilation number of up to 1.01 mu g C (mu g chl a)(-1) h(-1) under 21.4 W m(-2) UV-A alone (about half of noontime irradiance at the surface), about 40 % higher than nanoplankton (5-20 mu m). UV-B (280-315 nm) of 0.95 W m(-2) reduced the carbon fixation by approximately 20 and 57 % in microplankton and nanoplankton assemblages, respectively. In contrast, smaller picoplankton (< 5 mu m) was unable to utilize UV-A for the photosynthetic carbon fixation. In addition, only micro-sized assemblages demonstrated the UV enhancement on their primary productivity in the presence of PAR, by about 8 % under moderate intensities of solar radiation.